Media Usage Mapping in Accessing Information on Reproductive Health among Adolescents in West Java - Dida, Susanne; Lukman, Syauqy; Herison, Feliza; Priyatna, Centurion; Rifqi Zaidan, Arif; Sukarno; Prihyugiarto, Titut (International Journal of Psychosocial Rehabilitation, 2019)
In Indonesia, BKKBN (National Family Planning and Population Board) is responsible for providing information related to reproductive health towards Indonesians, adolescents included. This research proposes a study on reproductive health literacy, attempting to map the adolescents’ preferences of media and communication method related to dissemination of reproductive health information. This study aims to describe (1) the knowledge of reproductive health, (2) media preferences, (3) attitudes towards the media, and (4) communication behavior towards the media of adolescents in West Java. This study uses descriptive approach with a population of adolescents with a range of ages 18 to 24 years in West Java with a number of sample of 1006 respondents spreaded from all over West Java. This research employs a descriptive approach, with quantitative data obtained through questionnaire. The aim of this study is to map the patterns of information media usage behavior among adolescents in Java West. Through this research, an insight on the use of information media among adolescents when seeking reproductive health information is obtained. We believe that the findings can be used as a ground for policy making in optimizing information dissemination through the media to improve reproductive health awareness among adolescent.